ADAPTIVE CAPACITY TO CLIMATE CHANGE AND FOOD SECURITY AMONG FARM HOUSEHOLDS IN SOUTHWEST NIGERIA - Ibrahim, Shakirat; Omonitan, Michael; Aminu, Raheem; Oyawole, Funminiyi; Arowolo, Aisha; Ayinde, Idris (Economics of Agriculture, 2022)
Smallholder farming households represent one of groups most exposed to the vagaries of climate change because their production and livelihood depend on climatic elements. This study assessed the effect of climate change adaptive capacity on smallholder farming households’ food security in Oyo State, Nigeria. Data from 246 farming households were analysed using factor analysis to generate the Climate Change Adaptive Capacity Index (CCACI), Foster-Greer-Thorbecke Indices and Logit Regression. The most adopted adaptation strategies were intercropping, fallowing, fertilizer application, and crop rotation. Most of the households had moderate or high adaptive capacity to climate change. Econometric results show that farm households with low climate change adaptive capacity have a greater likelihood of being food insecure relative to farm households with moderate and high climate change adaptive capacity. These findings emphasize the need to enhance smallholder farmers’ capacity to mitigate the adverse effect of climate change on national food security.